Percepção da agroecologia e as manifestações sígnicas no contexto da produção orgânica da cooperativa agroindustrial oito de junho (Coperjunho) - Asturian, Rodrigo (2018)
Considering the complexity of agroecological production from a perspective of Sustainable Rural Development (DRS), the organic production of the agroecological bias of Cooperativa Agroindustrial Oito de Junho (Coperjunho) was studied, specifically in the sign manifestations coming from three different groups of farmers based on the National Agrarian Reform Program (PNRA): certificates for organic production, those in transition, and those that have returned to conventional agriculture. In the production of the sense of the Peasantry, the perception and generation of meanings are materialized through speeches, images and political convictions. The praxis in the relation of the farmer with the world that surrounds it allows the adherence of the Perspectivist Approach to Knowledge Assimetries and Polyocular Approach to the Dynamics and Governance of Organic Agriculture in the agricultural practice of the Coperjunho and of the farmers settled in the Project of Settlement (PA) Oito de Junho. In addition, the condition of distinction and notion of exceptionality affect the perception of these farmers regarding organic production. Thus, the creative capacity of the farmer as a Chayanovian utopia brings the emergence of the peasant principle and demonstrates the prevalence of the logopoietic perspective - in which the meaning is seen as a self-organizing principle - among the settlers with a greater degree of commitment in the organic production with agroecological principles. Keywords: Agroecology. Sustainable Rural Development. Organic agriculture. Land reform. Utopia. Cooperativism. Participative Certification. Semiotics. Peirce. Perspectivist and Polyocular Approach. Asymmetries of Knowledge. Meaning. Logopoietic.